Predictors of Swimming Ability among Children and Adolescents in the United States - Jennifer Pharr; Carol Irwin; Todd Layne; Richard Irwin (MDPI AG, 2018)
Swimming is an important source of physical activity and a life skill to prevent drowning. However, little research has been conducted to understand predictors of swimming ability. The purpose of this study was to understand factors that predict swimming ability among children and adolescents in the United States (US). This was a cross-sectional survey conducted between February and April of 2017 across five geographically diverse cities. Participants were accessed through the Young Christian Men's Association (YMCA) and included parents of children aged 4-11 years old and adolescents aged 12-17 years old. Independent t-test, analysis of variance (ANOVA), and univariate and multivariate analyses were conducted. Several factors were significant (p ≤ 0.05) predictors of swimming ability and explained 53% of the variance in swimming ability. Variables that were positively associated with swimming ability included: ability of parent(s) to swim, child/adolescent age, a best friend who enjoys swimming, water-safety knowledge, pool open all year, and encouragement to swim from parent(s). Variables that were negatively associated with swimming ability included: fear of drowning, being African American, and being female. Interventions and programs to improve the swimming ability of children and adolescents could be developed with these predictors in mind.